The Effect of Pester Power Variables on Parents' Decision to Buy Ice Cream Brand Walls at Alfamart Sriwijaya - Mataram - Asri Oktiani; I Gusti Putu Bagus Suastina; Herry Syafhariawan (SENTRALISASI, 2022)
The purpose of this study was to determine whether pester power which consists of peer influence variables, emotional pestering, persuasive pestering on parents' decisions to buy ice cream walls. Data collection was obtained from questionnaires distributed to 101 respondents obtained by the accidental sampling method. Respondents are parents of children aged 3-9 years who purchase ice cream walls from October to December 2021. This study is quantitative and uses SPSS 23 to process primary data obtained from respondents' answers. From the results of the study, it was found that all variables in the study had a significant influence on parents' decisions both simultaneously and partially and the Emotional Pestering variable became the dominant variable.